Enhancing the shariah governance framework for Malaysian IFIs through effective management strategies - Harun, Hafiza; Abdullah, Nurdianawati Irwani (DergiPark Akademik, 2017)
This research paper explores the practical adoption which could be applied to the theoretical analysis and viable recommendation for further enhancement of the Shariah Governance Framework by all management teams in the Malaysian Islamic Financial Institutions. In complementing this study, a set of questionnaires is distributed to some selected group of staff in a Takaful Operator in Malaysia to gauge their understanding of the subject matter. The effective and efficient organization needs to be embedded with a strong rapport between top management and another level of subordinates. This synergy simultaneously builds a robust governance for the organization, especially in Islamic finance area.